Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/pharmaceutics15030845
|View full text |Cite
|
Sign up to set email alerts
|

CD73-Positive Cell Spheroid Transplantation Attenuates Colonic Atrophy

Abstract: The incidence of inflammatory bowel diseases (IBD) is increasing worldwide. Mesenchymal stem/stromal cells (MSCs) have immunomodulatory functions and are a promising source for cell transplantation therapy for IBD. However, owing to their heterogeneous nature, their therapeutic efficacy in colitis is controversial and depends on the delivery route and form of transplanted cells. Cluster of differentiation (CD) 73 is widely expressed in MSCs and used to obtain a homogeneous MSC population. Herein, we determined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…These findings support the notion that DN cells possess high adipogenic differentiation potential and significant fat content in 3D culture. Hisamatsu et al found that 3D culture-derived spheroids of CD73+ cells exhibited enhanced cellular characteristics and an upregulated expression of immunomodulatory genes when compared with 2D cells [68]. In the present study, there was a tendency for lipid droplets to accumulate more in CD344-SP than in DN in 2D culture and more in DN than CD344-SP in 3D culture.…”
Section: Discussionsupporting
confidence: 53%
“…These findings support the notion that DN cells possess high adipogenic differentiation potential and significant fat content in 3D culture. Hisamatsu et al found that 3D culture-derived spheroids of CD73+ cells exhibited enhanced cellular characteristics and an upregulated expression of immunomodulatory genes when compared with 2D cells [68]. In the present study, there was a tendency for lipid droplets to accumulate more in CD344-SP than in DN in 2D culture and more in DN than CD344-SP in 3D culture.…”
Section: Discussionsupporting
confidence: 53%